Lectio praecursoria: Huumaava äänten pauhu : Rovaniemen markkinoiden äänimaisema 1881–1930 - Niemelä, Marko (Musiikki, 2023)
Lectio praecursoria: Immersed in an Intoxicating Medley of Sound: The Soundscape of the Rovaniemi Fair from 1881 to 1930 This doctoral dissertation in cultural history examines the soundscape of the Rovaniemi Fair—a key site and an event that has historically embodied the town of Rovaniemi and the region of Lapland as a whole. I examine the meanings associated with sounds in different sources, and investigate how sound was used and for what purpose, and how the soundscape changed from the founding of the Rovaniemi Fair in 1881 to the founding of the new marketplace in 1930. I approach the topic through the framework of soundscape studies, research on mentalities, and cultural history. I combine perspectives from musical anthropology and history of mentalities with cultural sound studies and cultural history. Methodologically, my study draws in particular on cultural history. The data analyzed consist of texts in newspapers and magazines, literature of the period under study, and novels. The main focus is on data sources stemming from Northern Finland, but the dataset has been complemented by other relevant sources originating elsewhere and produced at different times. In this study, I also argue that the history of music in Northern Finland has remained largely understudied. For people of that time, the Rovaniemi Fair signified both work and celebration. I argue that mentalities that inform collective conceptions of reality can be identified in the texts dealing with the Fair. Two seemingly opposing mentalities—a mentality of carnival and that of control—coexisted and interacted against the backdrop of the Fair. Carnival as a soundscape meant lively merrymaking that allowed people to transcend the everyday; however, this took place within the framework of control imposed by legislation and cultural practices. The mentalities of carnival and control can be interpreted as being constructed dialogically as the sum of various attitudes. Together they can be seen to form a collective ethos and a mental ambience—the ...